Impact of Dividend Payout (DPO) on Market Value of Listed Petroleum Marketing Companies in Nigeria - Adamu Saleh, Ibrahim; Rabi’u Muhammad, Muhammad (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The dividend policy of firm determines what proportion of earnings is paid to shareholders and what proportion is ploughed back in the firm for reinvestment purposes. The aim of this paper is to ascertain the Impact of Dividend Payout on the Value of Listed Firms in the Nigerian Petroleum Marketing Industry. Five firms that were quoted on the Nigerian Stock Exchange (NSE) were selected as sample for the study. Annual Reports and Accounts of the sampled firms, Daily Official lists and Facts Books of the NSE for the period of 2007-2016 form the source of the data. Correlation and regression were used in analyzing the data base on parsimonious multiple regression model developed by Musa (2005). The major findings revealed a strong and direct relationship between the dividend payout of petroleum marketing firms in Nigeria and their market value of shares. This revealed that payment of dividend by petroleum marketing Companies in Nigeria positively influence the market price of their shares. The major recommendation given is that management need to identify the shareholder’s interest in setting up a dividend policy that would balance their needs and retention for recapitalization to maximize value of the Companies.